The Correlation Between Watching English Videos And Students’ Listening Comprehension - Dwi Andi Maryanto (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
ABSTRACT: Listening is considered as the most basic amongst other language skills that encompass the ability to receive and comprehend the messages that is delivered through voice and sound in the communication process. The implementation of authentic material is essential in listening class in order to make the students familiar with how English are used in actual life. There are many ways to develop listening skills with the help of advances in technology. One of many methods where EFL learners are able to practice their extensive listening skills is by watching English based videos. Therefore, the researcher is interested in conducting research about the correlation of watching English videos frequency on students’ listening skills.This study used quantitative research method on two variables which are frequency of watching English videos, and English listening skill. The data for this research collected in the form of frequency of watching video questionnaire through Google Form to know how frequent the students watch English videos at home. Moreover, the researcher also collected listening comprehension score from 2nd semester of English department at the University of Islam Malang from the listening lecturers. The data are analysed based on the mean of Likert scale in the questionnaire and correlated with students’ listening comprehension score using SPSS Pearson’s Correlation analysis.The result of the study indicates that most of the students are at high level of profile at all indicators of frequency of watching videos such as frequency, repetition and attitude. Moreover, the study also indicates significant correlation between students’ frequency of watching English videos and their listening comprehension skills. It can be concluded that all the students have high profile of watching English video frequency. Moreover, the more frequent the students watch English videos, the better their listening skills, and indicated that English authentic videos improve students’ listening skills. This study suggests that it is important to consider learning English actively while watching English videos. The next researcher should consider the relationship of watching English video frequency and other language skills such as speaking, writing, reading and grammar.Keywords: English videos, frequency, listening skill.